Probiotic potential of indigenous lactic acid bacteria isolated from spiny lobster (Panulirus sp.) - RAHMAD LINGGA; VERRY ANDRE FABIANI; ZULFARINA ZULFARINA; YURNALIZA YURNALIZA; NURZAIDAH PUTRI DALIMUNTHE; BRENDOFLIN KURNIAWAN; TITIK ANGRAHINI; SAWA KUSTARIA; GUSDUR GUSDUR (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Lingga R, Fabiani VA, Zulfarina, Yurnaliza, Dalimunthe NP, Kurniawan B, Angrahini T, Kustaria S, Gusdur. 2026. Probiotic potential of indigenous lactic acid bacteria isolated from spiny lobster (Panulirus sp.). Biodiversitas 27 (5): d270525. https://doi.org/10.13057/biodiv/d270525. Feed management represents a fundamental factor influencing the efficiency and sustainability of lobster aquaculture operations. The nutritional requirements of lobsters encompass essential macronutrients, including proteins, carbohydrates, and lipids, traditionally supplied through fresh or formulated feeds. This study investigated the probiotic potential of indigenous Lactic Acid Bacteria (LAB) isolated from the intestines of spiny lobsters (Panulirus sp.) to address feed-related challenges in lobster aquaculture. Five marine lobster intestines were used as samples for LAB isolation using the spread plate method onto de Man, Rogosa, and Sharpe Agar (MRSA) medium supplemented with 1% CaCO₃. From 39 initial isolates, eight distinct taxa belonging to Lactobacillus and Enterococcus genera were characterized through morphological, biochemical, and physiological analyses. The isolates exhibited LAB properties and were Gram-positive, with diverse morphologies (cocci, bacilli, and coccobacilli). Eight isolates namely LM1, LM4, LP2, LP3, LP4, LP12, LP40, and LP33 were selected for further probiotic potential testing. Physiological characterization revealed robust adaptability across varied environmental conditions, with growth sustained at temperatures between 27-45°C and pH levels ranging from 2.5 to 8.0. Antimicrobial assays demonstrated significant pathogenic inhibition, with LM04 showing the largest inhibition zone against Staphylococcus aureus (maximum zone 25.94±1.58 mm) and Escherichia coli (maximum zone 15.51±1.06 mm). Isolates LP40 and LP12 showed effectiveness against both Pseudomonas aeruginosa and Vibrio sp. Most isolates showed antibiotic resistance to chloramphenicol while maintaining intermediate sensitivity to tetracycline and ampicillin. Isolate LM1 showed the highest growth rate, with populations reaching 23.5×10⁸ CFU/mL, LP2 showed the highest adhesion capabilities (9.9%±0.09). Identification based on 16S rRNA gene analysis showed that isolates LP3 and LP12 were Enterococcus faecalis, whereas the other isolates were identified only based on phenotypic characteristics. These findings established the indigenous LAB from Panulirus sp. as a promising probiotic candidate, particularly for enhancing disease resistance in lobster aquaculture systems, while highlighting areas for future optimization.